Numerical Investigation of Pool Boiling Under Ocean Conditions with Lattice Boltzmann Simulation. Part Ⅰ: Heaving Condition - Zou, Qifan; Liu, Xiuliang; Hu, Yongyan; Chang, Yuxuan; Li, Pengkun (Frontiers in Energy Research, 2021)
Pool boiling is the heat transfer mechanism of many heat exchangers inside ocean nuclear power plants working in the complex marine circumstances. And ocean condition will create a new acceleration field other than gravity for the fluid, which induces some unique thermal-hydraulic characteristics. In this work, pool boiling under heaving condition is numerically simulated using multiple relaxation time (MRT) phase change lattice Boltzmann method (LBM). Firstly, the simulated results under static condition have been validated with recognized empirical equations, such as Rohsenow’s correlation at nucleate boiling, Zuber’s model and Kandlikar’s model about critical heat flux (CHF). Then, pool boiling patterns, boiling curve of time-averaged heat flux, transient heat flux and heaving effects on different pool boiling regions are investigated. The results show that pool boiling curve of time-averaged heat flux between heaving condition and static condition with middle superheat degrees are similar. Heat transfer under heaving condition at low superheat is somewhat enhanced, and it is weakened at high superheat, which leads to little smaller CHF with larger superheat compared with that under static condition. Moreover, distinct fluctuation of transient heat flux of pool boiling under heaving condition is found for all boiling regimes. Furthermore, the heaving condition shows both positive and negative effects on pool boiling heat transfer at high gravity and low gravity region, respectively. Besides, both larger heaving height and shorter period time bring out more violent heaving motion, and make greater impact on poll billing heat transfer.